Reaching key financial reporting decisions : how directors and auditors interact - Beattie, Vivien [ (Vivien A.)]; Fearnley, Stella; Hines, Tony (John Wiley & Sons, 2011)
"A fascinating behind-the-scenes examination of how agreement on key financial reporting issues is reached, this book provides insights into a vital process which is normally inaccessible to all but its participants. With unprecedented access to key participants, the authors draw on results of an extensive survey of finance directors, audit committee chairs and audit partners of UK listed companies and present nine company case studies where the researchers conducted face to face interviews with Finance Directors, Audit Committee Chairs and Audit Partners. The authors identify and analyze the process adopted between these three parties both in discussing and negotiating financial reporting and auditing issues, and in reaching the agreed financial reporting outcome"-- Provided by publisher